Effect of Calcineurin Inhibitors and Mammalian Target of Rapamycin Inhibitors on the Course of COVID-19 in Kidney Transplant Recipients - Hasbal, Nuri Baris (Ann Transplant, 2021)
Coronavirus disease 19 (COVID-19) has been an ongoing pandemic since December 2019. Unfortunately, kidney transplant recipients are a high-risk group during the disease course, and scientific data are still limited in this patient group. Beyond the dosage of immunosuppressive drugs, pharmacological immunosuppression may also alter the infection response in the COVID-19 course. The effects of immunosuppressive agents on the development and process of infection should not be decided only by determining how potent they are and how much they suppress the immune system; it is also thought that the direct effect of the virus, increased oxidative stress, and cytokine storm play a role in the pathogenesis of COVID-19 disease. There are data about immunosuppressive drugs like calcineurin inhibitors (CNI) or mammalian target of rapamycin inhibitors (mTORi) therapy related to their beneficial effects during any infection course. Limited data suggest that the use of CNI or mTORi may have beneficial effects on the process. In this hypothetical review, the probable impacts of CNI and mTORi on the pathogenesis of the COVID-19 were investigated.